Implementation of Singing Method in Islamic Education Learning to Enhance Students' Learning Interest in Malaysian School - Nadia Amrul Ummah; Anip Dwi Saputro; Nurul Abidin (Universitas Islam Lamongan, 2025)
Students' interest in Islamic Religious Education (PAI) is often a challenge that affects the effectiveness of learning. Lack of engagement and motivation hinders the achievement of learning goals. To overcome this, the singing method was introduced as an innovative approach to create a more fun and interactive atmosphere. This study aims to explore the application of singing methods in PAI lessons to increase students' interest in SB At-Tanzil Kayu Ara in Malaysia. Using a descriptive qualitative approach, data were collected through interviews and documentation. The data analysis follows the Miles and Huberman model, including data reduction, presentation, and conclusions. Managers, teachers, and students are the main informants. The results of the research on the application of the singing method can increase students' interest. By implementing Islamic songs related to the lesson content creates a fun atmosphere, making it easier for students to understand and memorize the material while increasing their engagement. This method also increases students' confidence during learning. Thus, the singing method can be an effective alternative strategy to increase students' interest, especially in PAI lessons, and should be applied more widely in various educational settings.